Rút gọn các biểu thức: (2x - 5y)(2x + 5y) + (2x + 5y)^2; (x + 2y)(x^2 - 2xy +4y^2) + (2x - y)(4x^2 + 2xy + y^2)
Bài 2.33 trang 47 Toán 8 Tập 1: Rút gọn các biểu thức:
a) (2x−5y)(2x+5y)+(2x+5y)2
b) (x+2y)(x2−2xy+4y2)+(2x−y)(4x2+2xy+y2)
Bài 2.33 trang 47 Toán 8 Tập 1: Rút gọn các biểu thức:
a) (2x−5y)(2x+5y)+(2x+5y)2
b) (x+2y)(x2−2xy+4y2)+(2x−y)(4x2+2xy+y2)
a)
(2x−5y)(2x+5y)+(2x+5y)2=(2x+5y)(2x−5y+2x+5y)=(2x+5y).4x=2x.4x+5y.4x=8x2+20xy
b)
(x+2y)(x2−2xy+4y2)+(2x−y)(4x2+2xy+y2)=x3+(2y)3+(2x)3−y3=x3+8y3+8x3−y3=(x3+8x3)+(8y3−y3)=9x3+7y3
Xem thêm các bài giải SGK Toán 8 Kết nối tri thức hay, chi tiết khác: